Supporting Scenario-Based Product Design: the First Proposal for a Scenario Generation Support Tool - Anggreeni, I.; van der Voort, M. C. (Cranfield University Press, 2009)
Using concrete stories about product or technology use, or ‘scenarios’, is a promising design approach. Nevertheless, design practices face uncertainties especially in the activities of identifying, creating and selecting scenarios. Based on a workshop series at a design company, specific problem areas in its scenario practice have been identified. Support is required in: (1) documentation of design information and creation of scenarios from the information, (2) identification and selection of the scenarios for specific purposes, (3) concept evaluation using scenarios and (4) communication of scenarios to stakeholders. This paper proposes a functionality of the scenario generation support tool that addresses the requirements.
Organised by: Cranfield University
Keywords: Scenario-based product design; Product design; Scenario generation; Design practice; Support tool